All is not forgotten - Walker, Wendy, 1967- (New York : St. Martin's Press, 2016)
In the affluent town of Fairview, Connecticut, Jenny Kramer is attacked at a local party. She is given a controversial drug to medically erase her memory of the violent assault. But Jenny struggles with her raging emotional memory. Her father, Tom, becomes obsessed with his inability to find her attacker and her mother Charlotte, prefers to pretend this event did not happen. The fault lines within their marriage and their close-knit community emerge, and the quest to find the who invaded their town may just divide the town in two.
Keywords: Upper class families -- Connecticut -- Fiction; Young women -- Crimes against -- Fiction; Memory -- Fiction; Psychological fiction; Suspense fiction; Mystery fiction